Authors’ Human Rights and Copyright Policy - Austin, Greame W. (The Columbia Journal of Law & the Arts, 2017)
Few would likely disagree with the observation made by Graeme Dinwoodie in this journal some seventeen years ago that “[i]t is increasingly impossible to analyze intellectual property law and policy without reference to international lawmaking.” International instruments influence the shape of domestic intellectual property law, and, in turn, have become vehicles for exporting domestic norms. And international law can, and should, inform the interpretation of domestic statutes, including those in the area of intellectual property. This Article argues that human rights guarantees to protect authors’ moral and material interests should be included in the “international lawmaking” that is considered relevant to domestic intellectual property law and policy. In the analysis that follows, the phrase “authors’ human rights” is used to describe human rights commitments to protect authors’ moral and material interests in their work. The label “international intellectual property law” is used to denote the international instruments typically included in the “conventional list.” While this nomenclature will assist with the analysis, one of the key points advanced in this Article is that authors’ human rights should be considered a part of international intellectual property law, not separate from it.